EKONOMICZNE SKUTKI I METODY OGRANICZANIA BEZROBOCIA - Cieślukowski, Maciej (Wydział Prawa i Administracji UAM, 1998)
Positive as well as negative economic effects of unemployment and methods o f reduction o f it are presented in the article. Positive consequences of unemployment are first of all due to transient and short-time form of it and all profits come mainly to the employers. Since it is a fact that under unemployment the employees’ postulates for increased wages do diminish, a competition among workers grows up and the mobility of the man power gets bigger. Transient unemployment makes a reserve of labour potential which does increase the employers’ freedom of action. Negative consequences are produced first of all by long-term unemployment. It contributes, among others, to an increase in public expenses for social services for unemployed, to a reduction of budget income as a result of reduced income of the unemployed and further - to a drop of NBP (the State revenue) and to a development of the “gray zone”. Economic methods play fundamental role in fighting the unemployment; they are: defensive, immediately offensive and indirectly offensive. Offensive instruments that do create new places of employment should be of most important role in the policy of counteracting the unemployment. But also methods of relieving the effects of unemployment with allowances and acccessibility of social services should nevertheless be applied.
ECONOMIC EFFECTS AND METHODS OF REDUCING UNEMPLOYMENT